Nilai Nilai Dakwah Dalam Tradisi Maulid Nabi Muhammad SAW di Lombok - Burhanudin (Ulul Albab: Journal Da`wah and Social Religiosity, 2024)
The celebration of the Prophet Muhammad's birthday on Lombok Island contains various forms of da'wah values that can be practiced by the community in everyday life, including social values of society, beauty values, educational values, and various other da'wah values. In addition, using a qualitative descriptive research method, namely the author describes factually what is seen and found from the celebration of the Prophet Muhammad's birthday in the community on Lombok Island supported by the results of observations, interviews, and documentation studies that have been conducted by the author on Lombok Island. From the results of this study it was found that the values of da'wah in the tradition of the Prophet Muhammad's birthday such as: Values of beauty, spiritual values, moral values, values of cooperation or mutual cooperation and social. The tradition of the Prophet Muhammad's birthday is a good thing in Islam. In it is written the history of the life of the Prophet Muhammad which is so noble that it can be a good example in everyday life. Activities like this can be a motivator with a religious nuance in community life in the midst of moral degradation in Indonesia. The tradition of the Prophet Muhammad's Birthday in Lombok is not only a ceremony, but also an effective means of preaching to instill Islamic values. Through this activity, the values of goodness, brotherhood, exemplary behavior, and simplicity of the Prophet are conveyed to the community in a way that is in accordance with local culture, so that they can be understood and applied in everyday life.